SU(2) hadrons on a quantum computer via a variational approach - Yasar Y. Atas (Nature Portfolio, 2021)
Quantum simulations of lattice gauge theories are in principle scalable, but their extension to dynamically coupled matter has proven difficult. In this work, the authors use a variational quantum eigensolver to simulate a non-Abelian LGT including the effects of both gauge fields and dynamical fermions.